The Influence of Work Environment and Self-Reward on Employee Job Satisfaction at PT Sun Berlian Motor Rantauprapat - Syafaruddin Munthe; Wahyu Azhar Ritonga (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to determine the influence of work environment and self-reward on employee job satisfaction at PT Sun Berlian Motor Rantauprapat, simultaneously. The population in this study were employees at PT Sun Berlian Motor, the determination of the sample technique used Arikunto's opinion with a total of 50 people and the analysis method used was descriptive analysis method, multiple linear regression analysis, and hypothesis testing. The results of simultaneous hypothesis testing (F test) showed that the work environment (X1) and self-reward (X2) had a significant effect on employee job satisfaction, with an F count of 17.408 while the t table was 3.10 (F count is greater than F table). The results of the determination coefficient (R2) test showed an Adjusted R square value of 0.426 or 42.6% indicating that the work environment and self-reward simultaneously contributed to employee job satisfaction by 42.6%.